Use of the Virtual Laboratory for Training Specialists in the Field ff Laboratory Diagnostics - D.V. Rotar; S.Ye. Deineka; A.V. Humenna; N.D. Yakovychuk (Zaslavsky O.Yu., 2016)
The ways and possibilities of using the virtual laboratory at the classes in microbiology, virology, immunology with the techniques of microbiological researches for students major in laboratory diagnostics were discussed in the article. Given the limitations of the impromptu laboratory within the classroom, we have compared all aspects of the rational obtaining the practical skills by the students. We have analyzed the criteria that determine the use of electronic resources for the educational purposes to teach students at the department of microbiology and virology.